CROSS CULTURAL SPEECH ACTS OF INDIRECT REQUEST IN AN EFL CONTEXT - Perdhani, Widya Caterine; Hartono, Didik; Grace, Dita; Ubadillah, Ardafa Rizko; Annisa’, Indriyani (English Review: Journal of English Education, 2024)
This research aims to investigate the cross cultural among the L2 students that they have problems on indirect request in EFL context. The participants are students come from 2 different region between Malang, East Java and Palembang, South Sumatera. The indication of this research is the students were facing lacks on using L2 during their written area. This study uses written role play by DCT, to test how they were respond or analyze the questions were given. The participants from two different regions have different style to express their utterances in answering the questions. The results of this research that Javanese participants tend to explain everything in accordance to their manner, different from Sumatera which more answer directly. In different situation, for asking a help, Javanese participants are using hedged performative and later query prepatory, while Sumateran participants tend to using query prepatory to get a help. By mutual relationship situation, the Javanese participants use hedged performative and aware having closed relation, while the Sumatera participants are query prepatory strategy applied. Finally, from this research, it can be inffered that Java participants use strategy in giving respond, while Sumatera reduce kinship for respond situation.